Participatory research to elicit gender differentiated knowledge of native fruit trees - Muhammad, F.A.; Elias, Marlène; Lamers, H.; Omard, S.; Brooke, P.; Hussin, M.H. (Bioversity International, 2017)
Both men and women have specific local ecological knowledge of native fruit tree species. Excluding women from research-for-development initiatives is problematic because it can limit their access to the benefits derived from improved managemnet and use of fruit diversity. A study was conducted to better understand the ecological, organizational and marketing aspects of native fruit trees in Sarawak, Malaysia. Participatory research tools were used to explore the knowledge of both women and men about forest resources and benefits.